PERILAKU MEMBUANG SAMPAH DI KELURAHAN TAGARAJA KECAMATAN KATEMAN KABUPANTEN INDRAGIRI HILIR PROVINSI RIAU - Indah Oktavia; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT The problem of waste is a behavior faced by the people of Tagaraja Village, there are two focus problems in this thesis, namely (1) How is the behavior of the community in disposing of garbage in Tagaraja Village, Kateman District, Indragiri Hilir Regency, Riau Province? and (2) The impact of garbage accumulation in Tagaraja Village, Kateman District, Indragiri Hilir Regency, Riau Province?. While the research objectives of this study are to find out the people who dispose of garbage in the Tagaraja Village and to find out the impact of garbage accumulation. To answer the problems raised by researchers regarding the behavior of people disposing of garbage, researchers used qualitative research methods. From the results of research conducted by researchers in the field, it was found that the community in Tagaraja Sub-District managed waste by disposing of waste in 4 points, namely on the banks of the river, in ditch 7, on the PLN road, and in small ponds. The researcher uses James S. Coleman's rational choice theory. This is because the Tagaraja Village does not have TPS and does not have a large yard. Keywords: Garbage Disposal Behavior, Waste Management, Impact of Garbage Piling.